2002
DOI: 10.1074/jbc.m206033200
|View full text |Cite
|
Sign up to set email alerts
|

Klotho Protein Deficiency Leads to Overactivation of μ-Calpain

Abstract: The klotho mouse is an animal model that prematurely shows phenotypes resembling human aging. Here we report that in homozygotes for the klotho mutation (kl ؊/؊ ), ␣ II -spectrin is highly cleaved, even before the occurrence of aging symptoms such as calcification and arteriosclerosis. Because ␣ II -spectrin is susceptible to proteolysis by calpain, we examined the activation of calpain in kl ؊/؊ mice. m-Calpain was not activated, but -calpain was activated at an abnormally high level, and an endogenous inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 53 publications
3
31
1
Order By: Relevance
“…Hyperactivation of calpain causes damage to renal epithelial cells in Klotho-deficient mice (17). We observed that calpain and caspase-3 activities against exogenous substrate in the aorta from Klotho-deficient mice were 130% and 35% higher, respectively, than in WT mice ( Fig.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Hyperactivation of calpain causes damage to renal epithelial cells in Klotho-deficient mice (17). We observed that calpain and caspase-3 activities against exogenous substrate in the aorta from Klotho-deficient mice were 130% and 35% higher, respectively, than in WT mice ( Fig.…”
Section: Resultsmentioning
confidence: 62%
“…2A). Calpain activities were evaluated further by determining the endogenous level of αII-spectrin, a cleaved substrate fragment that is highly sensitive to calpain (17). αII-spectrin is cleaved at particular site by calpain, yielding a 136-kDa fragment (N-terminal cleaved products) and a 148-kDa fragment (C-terminal cleaved products).…”
Section: Resultsmentioning
confidence: 99%
“…BDA‐410 is a synthetic Leu‐Leu peptidomimetic that significantly attenuates various disease conditions (Carragher, 2006), including memory and synaptic transmission in a mouse model of Alzheimer disease and signs of premature aging in a mouse model of kotho deficiency (Manya et al ., 2002; Trinchese et al ., 2008). BDA‐410 strongly and reversibly inhibits cysteine proteases but not serine or aspartic proteinases.…”
Section: Discussionmentioning
confidence: 99%
“…When disrupted, ␣-Klotho, a regulator of calcium metabolism in the plasma membrane, is associated with a premature aging-like phenotype including emphysema (16,26). Additionally, the lack of ␣-Klotho induces hyperfunction of renal tubular 1␣-hydroxylase resulting in an abnormal increase of serum Ca 2ϩ , which activates the calcium-dependent matrix proteases such as calpain and induces emphysema (29). We anticipate a need to examine the possible role of intracellular calcium homeostasis as well as oxidative stress in the development of aging-like phenotypes in SMP30 KO mice.…”
Section: Discussionmentioning
confidence: 99%